APPLICATION OF FINANCIAL STATEMENT PREPARATION BASED ON FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES IN MSMES (CASE STUDY OF TOKO ANJANI COLLECTION) - Pebri Anjani; Nurhayati Nurhayati (Jurnal Ekonomi, 2023)
This research is entitled " Application Of Financial Statement Preparation Based On Financial Accounting Standards For Micro, Small And Medium Entities In MSMEs (Case Study Of Toko Anjani Collection)" which aims to help Toko Anjani Collection compile financial statements for micro, SME and small enterprises. Corporate Accounting Standards (SAK EMKM). This study used qualitative descriptive methods to collect data and compare Toko Anjan's financial statements with current accounting standards. Based on the survey results, Anjan's understanding of SAK EMKM is still limited and still maintains very simple financial books. The application of financial reporting based on SAK EMKM in the Toko Anjani collection has a positive effect as material for evaluating business development and making clear financial information.